1981
DOI: 10.1161/01.hyp.3.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemodialysis on blood volume distribution and cardiac output.

Abstract: SUMMARY Effects of hemodialysis on extracellular fluid volume distribution, left ventricular volumes, and cardiac output were determined In patients with end-stage renal disease (n = 19). Distribution of extracellular fluid loss from hemodialysis differed widely among patients, so that weight change correlated weakly with contraction of total blood volume (index of determination 29%, p < 0.05). End-diastolic volume (EDV) decreased from 150 ± 49 ml (mean ± SD) to 118 ± 42 ml, p < 0.001; stroke volume (SV) decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…The cardiac alteration documented is attributable to chronic increased cardiac work, that can be caused by sodium and water retention, presence of AVF, arterial hypertension and anemia [21] . Other authors have shown that the interdialytic body weight increment (the index of sodium and water retention), directly correlates with LV mass [22] ; in our patients, however, this value did not change during the study. Similarly, the fl ow rate in the vascular access remained unvaried.…”
Section: Discussioncontrasting
confidence: 77%
“…The cardiac alteration documented is attributable to chronic increased cardiac work, that can be caused by sodium and water retention, presence of AVF, arterial hypertension and anemia [21] . Other authors have shown that the interdialytic body weight increment (the index of sodium and water retention), directly correlates with LV mass [22] ; in our patients, however, this value did not change during the study. Similarly, the fl ow rate in the vascular access remained unvaried.…”
Section: Discussioncontrasting
confidence: 77%
“…Within the frequent dialysis group, interdialytic weight gain was associated with neither changes in LV mass (6) nor changes in LVEDV (7). These findings are similar to those of an earlier study that found no significant correlation between changes in total volume and changes in LVEDV (22). On the basis of this finding, we propose that changes in LVEDV induced by hemodialysis may not be related solely to changes in total blood volume, which would be reflected in changes in the interdialytic weight; decreased LVEDV may also result from a peripheral relocation of the blood volume away from the heart.…”
supporting
confidence: 90%
“…Observational studies in ESRD suggest that solute and water retention contribute to hypertension, LV hypertrophy, and congestive heart failure (23). The presence of a dilated ventricle (as measured by LVEDV) has been associated with much higher risk than the risk predicted by elevation in LVM alone (2,3).…”
Section: Discussionmentioning
confidence: 99%